2010
DOI: 10.1007/s00330-010-1785-8
|View full text |Cite
|
Sign up to set email alerts
|

Multi-detector CT urography: effect of oral hydration and contrast medium volume on renal parenchymal enhancement and urinary tract opacification—a quantitative and qualitative analysis

Abstract: Oral hydration leads to lower attenuation values in the urinary tract but improves the continuous opacification of the tract. Increase in contrast medium volume leads to higher renal parenchymal enhancement as well as to an increased continuous opacification of the urinary tract. Decrease in contrast medium volume cannot be compensated for by oral hydration in terms of parenchymal enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…[22] Oral hydration decreases the attenuation values in the urinary tract at the excretory phase, but improves the continuous opacification of the ureter. [23] Limitations There were limitations to our study. Patients were placed consecutively into the groups.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Oral hydration decreases the attenuation values in the urinary tract at the excretory phase, but improves the continuous opacification of the ureter. [23] Limitations There were limitations to our study. Patients were placed consecutively into the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although peroral hydration [13] and IV furosemide [9,14] are more definitively associated with improved urinary tract opacification than IV saline administration [10,15,16], we choose to use all three methods because they are all safe, low cost, and conveniently administered. Although the 7-minute delay used for urographic phase acquisition was determined largely on the basis of institutional experience and workflow efficiency, Kemper et al [17] experimentally validated precisely 7 minutes as the median urographic phase delay required for maximal distal ureteral opacification.…”
Section: Patel Et Almentioning
confidence: 99%
“…In terms of peroral hydration, Szolar et al [13] reported urinary tract opacification in patients undergoing CT urography supplemented with peroral hydration (at varying doses of IV contrast agent), using a scoring system slightly modified compared with ours. For instance, in their study, a score of 3 equaled 76-100% opacified segment.…”
Section: Patel Et Almentioning
confidence: 99%